PEACEFUL SETTLEMENT OF INTERNATIONAL AS WELL AS POLITICAL AND RELIGIOUS DISPUTES (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
Peaceful Settlement of International as well as Political and Religious Disputes.In the 76 years that have passed since the adoption of the United Nations Charter, the international society continues to face disputes and situations regarding interstate relations that it tries to resolve by peaceful means or, as the case may be, by resorting to force. Conflicts are an inevitable reality of relations between states, as inevitable as in the case of interpersonal relations. Often, states can pursue the same finality, but the ways of achieving the goal pursued or the claims that are raised differ, a factor that can lead to the arisal of conflicts.In the process of peaceful settlement, states enjoy full freedom of choosing the means of peaceful settlement, in such a way that they correspond to the characteristics of the dispute and ensure its resolution. Thus, the subjects of international law have a wide range of possibilities, starting from simple consultations and up to jurisdictional means. Peaceful settlement instruments can be used at any time, regardless of the order, but states have the obligation to act in good faith in order to find a solution to end the conflict.